Territorial vs. Worldwide Corporate Taxation : Implications for Developing Countries - Matheson, Thornton (IMF Working Papers; Working Paper ;, 2013)
Global investment patterns mean that effective taxation of foreign investors is of increasing importance to the economies of lower income countries. It is thus of considerable concern that the historical framework for cross-border income tax arrangements is not always well suited to allow low-income countries (LICs) effectively to generate tax revenues from profits on foreign direct investment (FDI). Several aspects of this framework contribute to the problem. This paper discusses, in particular, the likely effect of a shift by major economies from the system of worldwide corporate taxation toward a territorial system on the volume, distribution, and financing of FDI, focusing on LICs. It then empirically analyzes bilateral outbound FDI data for the UK for 2002-10 to determine whether the move to territoriality made corporations more sensitive to hostcountry statutory tax rates. Supporting evidence for this hypothesis is found for FDI financed from new equity.